Identification of types of compounds from Pereskia bleo (Cactaceae) extracts - Ahmad Faiz Mohammad Zulkifli (2015)
This thesis was done for the purpose of identifying the types of compounds that present in the Pereskia bleo extracts. The distribution of Pereskia species are widely spread in the Carribean, Central and South America in a range of drier forest habitats The common characteristics of Pereskia are broad, flattened leaves with C3 photosynthesis, having superior to inferior ovaries, areoles with leaf production, dense fibrous wood, poorly developed stem epidermal and hypodermal layers, and nonsucculent tissues. Commonly known as `Jarum Tujuh Bilah', Pereskia bleo can be easily confused with their contrast, Pereskia grandifolia. They can be distinguished through the leaves, flowers and spines, in which Pereskia grandifolia has thicker, uncorrugated leaves, longer and lesser spines and purplish-pink flowers whereas Pereskia bleo has thinner, corrugated leaves, shorter spines and orangish-red flowers. This research was carried out to identify the types of compounds that present in the Pereskia bleo extracts. Several type of compounds was identified but not with 100% certainty due to the lack of proper statistical analysis. Some of the types of compounds identified are sterols, alkaloids, terpenes and flavoniods. High performance liquid chromatography (HPLC) analysis was done to further confirm and identify the type of compounds that present in the hexane Pereskia bleo extracts. 3 highest peaks was analysed and compared with previous literature value.